THE INFLUENCE OF FINANCIAL CRISIS AND FINANCING DECISION ON INVESTMENT DECISION IN INDONESIAN MANUFACTURING COMPANY - Yunardi, Eric Evan (Research In Management and Accounting (RIMA), 2018)
At the time of the global financial crisis, many companies throughout the world were affected, making it difficult for companies to make financing decisions on their activities in conducting business activities and also followed concerns in making investment decisions. This is because at the time of the crisis and after the global financial condition was still not stable. The purpose of this research is to find out whether the global financial crisis influences company decisions in financing their activities in conducting business activities and in making investment decisions. The number of samples in this study were 94 Indonesian manufacturing companies with 752 data points listed on the Indonesia Stock Exchange. Data used from 2004 to 2011. Data analysis techniques used were Difference-in-means before and after global financial crisis with Stata as the statistical tool. The result of this research is the global financial crisis have positive and direct impact on investment decision in Indonesian manufacturing companies. Indonesian manufacturing companies also enjoyed surplus of capital inflows from the shock caused by global financial crisis which decrease the debt to equity ratio. But the opposite, financing decision have indirect and negative effect on investment decision in Indonesian manufacturing companies.